PERAN KELOMPOK WANITA TANI TERHADAP EFEKTIFITAS PROGRAM P2L DALAM MENINGKATKAN KETAHANAN PANGAN DI ACEH UTARA - Cut Rozana Sari; Hafni Zahara; Fadli Fadli; Emmia Tambarta Kembaren; Muhammad Yusra; Nopri Yanto; Rinaldi Rinaldi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2026)
This study was motivated by the conditions in the Syamtalira Aron community in North Aceh, where most people depend on agriculture for their livelihoods yet still face challenges regarding household food security. This is partly due to the suboptimal use of yard space, low levels of technical assistance, and minimal involvement of women. The study examines the role of Women Farmers Groups (KWT) in implementing the Sustainable Food Backyard Program (P2L) in Syamtalira Aron District, focusing on planning, implementation, and evaluation activities in North Aceh Regency. This study focuses on members of Women Farmers Groups in Syamtalira Aron District, North Aceh Regency. This study employed a descriptive research method. The results show that the KWT plays a strategic role in implementing the P2L program, particularly in planning and implementation, both of which received high ratings. KWT members' active participation in determining crop types, preparing planting schedules, and managing yards reflects participatory principles and increases household food self-sufficiency. Their participation in implementation also strengthens social solidarity and family food security. However, the program evaluation is still in the adequate category, with informal and unsystematic practices. This hinders the program's sustainability. Women play a significant role in this program, not only as technical implementers, but also as strategic decision makers. This contributes to increasing the availability, accessibility, and utilization of nutritious and diverse food, aligning with national food security objectives.